Perkembangan Tasawuf dalam Sejarah Peradaban Islam - Al-Badani, Abd Quddus (TSAQOFAH, 2021)
Every human being basically has potential, namely the ability to acquire "knowledge" without going through the sensory and intellectual processes. It's just that the potential is different for each person depending on the intensity of the syiddah and dhu'f that exist in him. In fact, that potential is often "hidden" in the corner of his unconscious, so that it cannot be actualized. Philosophers call it ontologie (the science of being), or metaphysics (which is behind the veil of reality). So the main humans are divided in looking for something that exists. One with a way of thinking, by writing to the exact sciences, logic and so on. And another by way of feeling, by way of zauq. Thanks to the sincerity of his heart, while the first group was still searching, which sometimes met the corners of the truth, and sometimes stumbled into other paths, the two contemplated in the realm of taste, and they were satisfied with that taste.